Effectiveness of Integrated Licensing Service Information System Services (SIPPAU) in Application for Building Permits (IMB): Efektivitas Pelayanan Sistem Informasi Pelayanan Perizinan Terpadu (SIPPAU) Dalam Pengajuan Izin Mendirikan Bangunan (IMB) - Komalasari Kariadi, Sofi; Riyadh UB, Ahmad (Indonesian Journal of Public Policy Review, 2022)
This study aims to analyze and describe the effectiveness of the Integrated Licensing Service Information System (SIPPADU) in applying for a Building Permit (IMB) at DPMPTSP Sidoarjo Regency. The method in this study uses qualitative research methods with descriptive methods. The collection technique uses interview, observation, and documentation techniques. The data analysis technique used by Miles and Huberman consists of four components of analysis, namely data collection, data reduction, data presentation, and drawing conclusions. The results of this study show the conclusion that the Integrated Licensing Service Information System (SIPPADU) in applying for a Building Permit (IMB) at DPMPTSP Sidoarjo Regency in terms of service efficiency in completion time needs to be evaluated while the responsiveness of officers, facilities and infrastructure, the spirit of cooperation and loyalty of the working group, and the relationship between the leader and subordinates is appropriate.